PENGARUH PAKAN YANG BERBEDA TERHADAP PERTUMBUHAN BENIH IKAN GABUS (Channa gacua) - fani, Fariedah; S., Widodo M. (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2016)
The purpose of this research was to know the suitable food for snake head fry rearing. This research used experimental method with completely randomized design with three treatment: A (used Artemia sp.), B (used Daphnia sp.) and C (used Tubifex sp.), each treatment was replicated 3 replication. Major parameters was growth rate and specific growth rate while minor parameters was temperature, dissolved oxygen and pH. The result showed that treatment C which used Tubifex as feed resulted the highest growth rate with 1.25 %/day and also the highest of spesific growth rate was resulted from treatment C which used Tubifex as feed with 1.39 %/day. This was caused that protein content in Tubifex was the highest than in Artemia and Daphnia (63.05 %). Protein was the major nutrient that affected fish growth performance. Protein supplied essential and non essential acid amino that needed to muscle formation and enzimatic function, beside that protein also had a role to energy availability preservation. The result of water quality measurement showed that water quality was suitable for snake head fry growth. Water quality toward that temperature between 20 oC - 27 oC, DO 3 - 4,50 mg/L and pH range from 5 to 8.42